2013
DOI: 10.3928/23258160-20130909-07
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Hypertension and Intraocular Pressure Asymmetry After Intravitreal Injection of Anti–Vascular Endothelial Growth Factor Agents

Abstract: Elevated IOP may occur after ranibizumab or bevacizumab injections, often exhibiting a delayed and perhaps cumulative effect. The authors found significant bilateral IOP asymmetry in patients developing unilateral glaucoma after VEGF-inhibitor injections, a potential early indicator or proxy for pathologic IOP elevation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 39 publications
0
22
1
2
Order By: Relevance
“…74,75 While some patients respond to intravitreal injection with sustained elevation of IOP, most do not even after multiple injections. [76][77][78][79][80][81][82] In our study, we performed intravitreal injection of drug-loaded NS once and observed IOPlowering effects out to 32 days (Fig. 4).…”
Section: Discussionmentioning
confidence: 62%
“…74,75 While some patients respond to intravitreal injection with sustained elevation of IOP, most do not even after multiple injections. [76][77][78][79][80][81][82] In our study, we performed intravitreal injection of drug-loaded NS once and observed IOPlowering effects out to 32 days (Fig. 4).…”
Section: Discussionmentioning
confidence: 62%
“…Most studies report a return to baseline by 30-min post-procedure. There is also a suggestion of longterm IOP elevation in those with repeated antivascular endothelial growth factor injections, [15][16][17][18][19][20][21][22][23][24] although this is not universally accepted. 25,26 Studies have been performed on cadaver eyes to measure pressure changes with intraocular injections although these were performed decades ago, with different needle gauges and volumes than are currently used for common intravitreal injections.…”
Section: Introductionmentioning
confidence: 99%
“…59 Considering sustained IOP elevation may increase the risk of developing glaucoma, further evaluation of a possible association between repeated intravitreous anti-VEGF injections and sustained IOP elevation is indicated. 5, 6, 1013 An exploratory ad hoc analysis that assesses whether repeated intravitreous injections of ranibizumab increase the risk of sustained elevation in IOP or initiation or augmentation of IOP-lowering treatment in eyes with DME compared with eyes receiving focal/grid laser through 3 years is reported herein.…”
Section: Introductionmentioning
confidence: 99%